2007
DOI: 10.2217/17435889.2.6.789
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nanoparticles for Therapeutics

Abstract: Nanotechnology offers many advantages to traditional drug design, delivery and medical diagnostics; however, nanomedicines present considerable challenges for preclinical development. Nanoparticle constructs intended for medical applications consist of a wide variety of materials, and their small size, unique physicochemical properties and biological activity often require modification of standard characterization techniques. A rational characterization strategy for nanomedicines includes physicochemical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
251
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(264 citation statements)
references
References 67 publications
0
251
0
2
Order By: Relevance
“…From the TEM images, an average particle diameter and standard deviation of 17.8 and 1.7 nm, respectively, were recorded for the citrate-capped AuNPs, compared to 17.9 and 1.9 nm, respectively, for the AuNPs functionalized with 16.8 μg/ml of PEG. It was expected that no significant difference in size between citrate-and PEG-capped AuNP would be observed via TEM, as only the gold core is visible at the acceleration voltage used [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the TEM images, an average particle diameter and standard deviation of 17.8 and 1.7 nm, respectively, were recorded for the citrate-capped AuNPs, compared to 17.9 and 1.9 nm, respectively, for the AuNPs functionalized with 16.8 μg/ml of PEG. It was expected that no significant difference in size between citrate-and PEG-capped AuNP would be observed via TEM, as only the gold core is visible at the acceleration voltage used [24].…”
Section: Resultsmentioning
confidence: 99%
“…The biological response can be altered using capping agents such as polyethylene glycol (PEG) also referred to as polyethylene oxide (PEO) [20,21], mercaptosuccinic acid, various proteins [21] or other biomolecules [2]. Such functionalization has led to an extensive research effort investigating AuNPs as carriers for a range of biomolecules and drugs [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the defective vascular architecture and poor lymphatic drainage, nanoparticles can extravasate through these gaps into extravascular spaces and accumulate inside tumor tissues (26,27). This phenomenon is known as the enhanced permeability and retention (EPR) effect (28,30), which has been generally observed in many types of solid tumors. Since the prepared MPEG-PCL is small enough (~20 nm), it can increase the selectivity of the available cytotoxic agents by delivering them specifically to tumor tissue, which allows maximal accumulation and the deepest penetration into tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have also shown that incubating NPs with human plasma, from subjects with different diseases and medical conditions, results in protein coronas of different composition [32]. Since blood composition is highly complex, the analysis of the NP behavior in complete (human) blood is very challenging and the studies are usually done in vitro using defined suspension conditions and/or in vivo experiments (for a review see Hall et al [33]). Indeed, most research is focused on the identification of surface adsorbed proteins on NPs with respect to their physicochemical properties [34].…”
Section: Bloodmentioning
confidence: 99%